Collision density: driving growth in urban entrepreneurial ecosystems - Nylund, Petra; Cohen, Boyd (International Entrepreneurship and Management Journal, 2017)
The growth of entrepreneurial ecosystems is becoming increasingly dynamic. We introduce the concept of collision density, defined as the potential frequency of interdisciplinary interactions, to explain this phenomenon. We develop hypotheses about the impact of collision density on the growth of entrepreneurial ecosystems. This impact is hypothesized to be amplified by the presence of angel financing. We find support for our hypotheses in panel data from 89 urban entrepreneurial ecosystems of 92,229 investments between 2007 and 2014. We conclude with discussions of the the implications for research and practice.
Keywords: Collision density; Entrepreneurial ecosystems; Urban entrepreneurship; Angel financing; Agglomeration economies